In Vitro Evaluation of Different Concentrations of Linoleic Acid on Hydrogenation Pattern of Fatty Acids by In-1 Strain of Butyrivibrio fibrisolvens - Shivani, Swati; Tyagi, A.K.; Srivastava, Anima; Gupta, Ritika; Dixit, Sonam; Sinha, S.K. (Indian Journal of Animal Nutrition, 2018)
In the present study, the effect of sunflower oil as a source of linoleic acid (LA) on production of conjugated linoleic acid (CLA) by anaerobic Butyrivibrio fibrisolvens In-1 bacteria was evaluated. Initially, B. fibrisolvens In-1 was inoculated in anaerobic ATCC media having same amount (250 Î¼g/ml of media) of four different dietary oils and incubated for 24 h. Supplementation of sunflower oil resulted in the highest CLA production by B. fibrisolvens In-1 among the treatments which was further used for in vitro study. Different concentrations of linoleic acid (0, 100, 200, 300, 400 and 500 Î¼g/ml of media) were used and incubated for different time intervals (0, 2, 4, 6, 8, 10, 24, 36 and 48 h) in ATCC anaerobic media. The highest CLA production (103.32 Î¼g/ml) was recorded with 400 Î¼g/ml linoleic acid at 8 h of incubation period and the maximum growth occurred when incubation was done with 100 Î¼g/ml free linoleic acid for 6 h and decreased further with time and increased linoleic acid concentration. The results indicated that higher concentration of linoleic acid had negative effect on the growth and CLA production potential of Butyrivibrio fibrisolvens In-1.